Aprender pela pesquisa: desafios do letramento informacional no ensino médio de uma escola estadual de Aparecida de Goiânia-GO - Mota, Jacqueline Pereira (2022)
Analyzes how the research process occurs by students in a state school in Aparecida de Goiânia-GO, considering the informational literacy for basic education in order to develop a necessary educational product. The work is based on the theoretical foundations of authors from the area of Librarianship and Information Science who study informational literacy, Beluzzo (2021), Campello (2009), Dudziak (2001, 2003) and Gasque (2012; 2020), authors who deal with school research as reconstructive questioning, Bagno (2000), Demo (2015) and other authors from the area of Education related to the theme. This is an exploratory-descriptive case study research, analyzed from a qualitative-quantitative methodological perspective with the application of a questionnaire has as research subjects 56 students of the third year of high school of the Nova Era State School. To evaluate the data collected it was used the theoretical basis of the reference process of the author of the area of Librarianship Denis Grogan (2001), which is designated as the recognition of an informational need to solve a question: a) problem; b) need for information; c) initial and negotiated question; d) strategy and search process. The results were analyzed using simple descriptive statistics with the help of the software Statistical Package for the Social Sciences (SPSS 20), and thematic content analysis. Among the results obtained it is possible to evidence that most students feel safe and with autonomy to solve information problems anchored in the facilities to search on the internet. The students recognize the importance of evaluating the information available on the internet and of citing references in the papers. We conclude that the research process in the high school of the Nova Era State School requires monitoring and guidance for a learning process based on information literacy, and we realize the need for training students to learn to use physical and digital information resources effectively. The result of this research is the development of an educational product in video format, entitled: "Animated video: how to do a good school research in high school", with the intention of introducing information that can help students in the development of skills for school and scientific research. As a contribution, the results of this dissertation can be used as a diagnosis for school managers, teachers and librarians to develop programs and projects of information literacy in high school focusing on mediation and guidance in school work, and thus enable the 'learning through research' integrating the areas of Librarianship, Information Science and Education.